2007
DOI: 10.1021/ja075076a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Ta(NMe2)5 with O2:  Formation of Aminoxy and Unusual (Aminomethyl)amide Oxo Complexes and Theoretical Studies of the Mechanistic Pathways

Abstract: Reaction of d0 Ta(NMe2)5 (1) with O2 yields two aminoxy complexes (Me2N)(n)Ta(eta2-ONMe2)(5-n) (n = 4, 2; 3, 3) as well as (Me2N)4Ta2[eta2-N(Me)CH2NMe2]2(mu-O)2 (4) and (Me2N)6Ta3[eta2-N(Me)CH2NMe2]2(eta2-ONMe2)(mu-O)3 (5) containing novel chelating (aminomethyl)amide-N(Me)CH2NMe2 ligands. The crystal structures of 2-5 have been determined by X-ray crystallography. (Me2N)4Ta(eta2-ONMe2) (2) converts to (Me2N)3Ta(eta2-ONMe2)2 (3) in its reaction with O2. In addition, the reaction of Ta(NMe2)5 with 3 gives 2 onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 57 publications
4
36
0
Order By: Relevance
“…Subsequent exchange between Ta-O-NMe 2 in 16 and Ta-NMe 2 in 12 gives 15. This exchange is similar to the exchange Ta(NMe 2 ) 5 (6) + (Me 2 N) 3 Ta(ONMe 2 ) 2 (8) 2 (Me 2 N) 4 TaO-NMe 2 (7) discussed earlier [12] . Reactions of both (Me 2 N) 4 Ta(SiBu t Ph 2 ) (12) The −Si(SiMe 3 ) 3 group is bulkier than the −SiBu t Ph 2 group, and it may prevent the formation of additional products in the reaction of (Me 2 N) 3 TaSi(SiMe 3 ) 3 (11) with O 2 , yielding just one product [26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Reactions Of O 2 With D 0 Amide Silyl Complexes (Me 2 N) 4 Tsupporting
confidence: 82%
See 2 more Smart Citations
“…Subsequent exchange between Ta-O-NMe 2 in 16 and Ta-NMe 2 in 12 gives 15. This exchange is similar to the exchange Ta(NMe 2 ) 5 (6) + (Me 2 N) 3 Ta(ONMe 2 ) 2 (8) 2 (Me 2 N) 4 TaO-NMe 2 (7) discussed earlier [12] . Reactions of both (Me 2 N) 4 Ta(SiBu t Ph 2 ) (12) The −Si(SiMe 3 ) 3 group is bulkier than the −SiBu t Ph 2 group, and it may prevent the formation of additional products in the reaction of (Me 2 N) 3 TaSi(SiMe 3 ) 3 (11) with O 2 , yielding just one product [26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Reactions Of O 2 With D 0 Amide Silyl Complexes (Me 2 N) 4 Tsupporting
confidence: 82%
“…Theoretical studies of the formation of the Zr complex 4 are presented. We have found that the reaction of Ta(NMe 2 ) 5 (6) with O 2 gives unusual oxo complexes (Me 2 N) 4 Ta 2 [η 2 -N(Me)CH 2 NMe 2 ] 2 (μ -O) 2 (9) and (Me 2 N) 6 Ta 3 [η 2 -N(Me)CH 2 NMe 2 ] 2 (η 2 -ONMe 2 )(μ -O) 3 (10) containing novel chelating -N(Me)CH 2 NMe 2 ligands as well as aminoxy complexes (Me 2 N) 4 Ta(η 2 -ONMe 2 ) (7) and (Me 2 N) 3 Ta(η 2 -ONMe 2 ) 2 (8) [12] . Density functional theory (DFT) studies suggest monomeric reaction pathways in the formation of 7-10 through peroxide intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that perhaps the C¼N bond in the imine produced by b-hydride elimination from one of the amido moieties may insert into the bond between the metal and a second amido ligand to form an (aminomethylene)amido, ÀN(CH 3 )CH 2 N(CH 3 ) 2 , ligand. 48,49 Hydrogenation of that new ligand would produce N,N,N 0 -trimethyldiaminomethane, the fourth product detected in the GC reported in Fig. 1.…”
Section: Resultsmentioning
confidence: 97%
“…[25][26][27][28][29][30][31][32] Furthermore, in the case of reaction between group IIIB organic compounds including TMA and oxygen, trimethylgallium ͑TMG͒ is reacted with oxygen as below 33 …”
Section: Resultsmentioning
confidence: 99%